Consumer Responses to Sustainable Product Labeling (Eco-label) in Purchasing Decisions - Kristian Panjaitan, Feliks Anggia Binsar; Sinaga, Hommy Dorthy Ellyany (Westscience Press, 2025)
This study examines consumer responses to sustainable product labels (eco-labels) and their influence on purchasing decisions in Indonesia. Using a quantitative research design, data were collected from 150 respondents through a structured questionnaire with a 1–5 Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to evaluate both the measurement and structural models. Results indicate that eco-label perception has a significant positive effect on consumer trust and purchasing decisions. Furthermore, consumer trust plays a mediating role, strengthening the relationship between eco-label perception and purchase behavior. Environmental awareness also emerged as a strong determinant of purchasing decisions, showing that consumers who are more environmentally conscious are more responsive to eco-labels. The model demonstrated substantial explanatory power (R² = 0.62) for purchasing decisions, confirming the importance of eco-labels, trust, and awareness in shaping sustainable consumer behavior in Indonesia. These findings provide practical implications for businesses and policymakers in promoting eco-labeled products and fostering sustainable consumption.